2023
DOI: 10.1002/lsm.23723
|View full text |Cite
|
Sign up to set email alerts
|

Melasma treatment with a 1064 nm, picosecond‐domain laser with a fractionated multibeam lens array

Eric F. Bernstein,
Lisa D. Basilavecchio,
Jenny Wang

Abstract: Background and ObjectivesPicosecond‐domain lasers have been fitted with fractionated optics for dermal remodeling. This study evaluates the safety and efficacy of a multiwavelength picosecond‐domain laser, using a 1064 nm multibeam lens array, for improving the appearance of melasma.Study Design/Materials and MethodsTwenty adults with a clinical diagnosis of melasma were enrolled and received 4 monthly 1064‐nm, 450 ps laser treatments delivered with a 10 × 10 fractional array of 150 µm microbeams. Cosmetic uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…The authors declare no conflict of interest. Manoj Pawar MD 1 Assel Satvaldinova MD 1 Mehak Singh MD…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors declare no conflict of interest. Manoj Pawar MD 1 Assel Satvaldinova MD 1 Mehak Singh MD…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…We read with great interest the nicely written article by Bernstein E et al 1 on-picosecond laser in melasma. We have been also practicing with the same laser i.e.…”
mentioning
confidence: 99%
“…The picosecond laser also has a 1064-nm wavelength and a large spot of >6 mm; therefore, we found that adopting a combination of large-spot lowfluence 1064-nm and fractional 1064-nm picosecond lasers to treat melasma is relatively safe and effective, which has been reported in many studies. 13,14 Picosecond lasers mainly produce photoacoustic effects, and the 'subcellular selective photothermal effect' has not been demonstrated in the treatment of melasma; therefore, we aimed to determine the mechanism by which picosecond lasers promote melanin metabolism for treating melasma.…”
mentioning
confidence: 99%